Estimation of conjugated dienes in gasoline by GC-MS. (18th October 2017) - Vijay, P.; Chopra, Aditi; Gopinath, M.; Rajmohan, K. S.
ABSTRACT: The monitoring of Hydrogenation Units in the refineries is important to monitor the sulphur levels as per the Euro-V / VI specifications laid down by European Union all over the world. The hydrogenation unit first removes the di-olefins from the gasoline and then removes sulphur by Desulfurization process to bring down total sulphur to 10 ppm in commercial gasoline in order to meet Euro-VI specifications. In addition, it is also targeted to maintain the Research Octane Number (RON) desired by the automobile manufacturers. A number of analytical techniques have been reviewed in this work to monitor the hydrogenation process in the petroleum refineries. The concentration of di-olefins is brought down to ppm level in the product. The possibility of using maleic anhydride condensation by University of Petroleum method no. 326 is also explored in the present work. A complete protocol is described to monitor the complete Hydrogenation process leading the production of Euro-V / VI gasoline.